Mother nature's two laws : ringmasters for circus earth : lessons on entropy, energy, critical thinking, and the practice of science - Kirwan, A. D. (World Scientific, 2000)
Every day brings a fresh barrage of bewildering claims about science and technology. How non-scientists tell the difference between the hyperbole and those developments that are important? With a modest amount of critical thinking, an understanding of how science is practiced, and a qualitative understanding of the two most sacred principles in science - the first and second laws of thermodynamics - anyone can make the distinction. Critical thinking and the practice of science are not emphasized in undergraduate science courses for non-scientists, while exposure to the first and second laws is.